Linguistic and Psycholinguistic Approaches on Implicatures and Presuppositions - Pistoia-Reda, Salvatore; Domaneschi, Filippo (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book discusses developments in the study of implicatures and presuppositions, drawing on recent linguistic and psycholinguistic literature. It provides original discussions of specific formal aspects of the theoretical reconstruction of these phenomena. The authors offer innovative experimental analyses in which crucial processing questions are addressed, and new experimental methodologies are introduced. The result is an advanced debate featuring broad empirical coverage of the issues, as well as an informed discussion of the connections between a Compositional Semantics and a Pragmatic Theory of Implicit Communication, in light of the empirical data coming from Experimental Semantics and Pragmatics. This book will be a worthwhile read for those with interests in both the formal and methodological aspects of these arguments.
Keywords: Linguistics.; Language and languages -- Philosophy.; Psycholinguistics.; Semantics.; Pragmatics.; elektronické knihy; electronic books